A green and highly efficient sulfur functionalization of starch. Issue 64 (12th July 2015) - Chauhan, Kalpana; Priya, Vishal; Singh, Prem; Chauhan, Ghanshyam S.; Kumari, Sapana; Singhal, Rakesh Kumar
<x xml:space="preserve">Abstract</x> An innovative green approach to achieve thiol functionalization of starch with a degree of substitution ≥ 2.